PENGARUH TINGKAT PELAYANAN TERHADAP KEPUASAN PENGUNJUNG PADA OBJEK WISATA MALINO HIGHLANDS KABUPATEN GOWA - Rasyid, Muh. Nur; Naidah, Naidah; Danil, Danil (Universitas Muhammadiyah Makassar, 2021)
This study aims to achieve an answer to the problem of the influence of visitor satisfaction on the tourist attraction of the Malino Highlands, Gowa Regency. The population of this study were visitors to the Malino Highlands tourism. The sample used is according to the wishes of 50 visitors. This type of research is quantitative research. The data techniques used were questionnaires and documentation. The data analysis method used is simple regression analysis. The simple linear results obtained Y = 3.601 + 0.216 means a constant value of 3.601 with a regression coefficient of 0.216 which states that the direction of the variable x to Y is positive and significant 0.000 0.05, which means that service has a significant effect on visitor satisfaction at the tourist attraction of the mountainous Malino Regency GowaKeywords: Level Of Service, Visitor Satisfaction